Alert Level 1 - Leceña, Hannah A. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 2 (2022): Dx Machina: Philippine Literature in the Time of COVID-19, 2024)
This is a flash-fiction collection about the life and experiences of teachers in the middle of the pandemic. It talks about ethics, politics, and the moral values of a teacher; who is also a person, a parent, a wife, a daughter, a lover, a voter, a bread-winner, a human who is just being herself/himself; and surviving